ANALYSIS OF THE RESULTS OF RESEARCH ON THE PROCESS OF CLEANING AND SORTING COTTON SEEDS - Maksad Ibragimovich Axmedov; Rakhimov Fayzullo Xusanboy ugli; Rejabboyev Sokhibjon Tojimirzayevich; Muradov Rustam Muradovich (Galaxy International Interdisciplinary Research Journal, 2023)
The main raw material of world textile production is cotton fiber. According to the International Cotton Advisory Committee (ICAC), in recent years, 23.07 million tons of cotton fiber have been produced in the world, and its consumption is 24.55 million tons. It is expected that the consumption of cotton fiber and the demand for it will increase in the future due to the intensively growing population. The increase in demand for cotton fiber, in turn, requires a constant improvement in its quality and production efficiency. In this regard, much attention is paid to increasing the competitiveness of cotton fiber in the world market, modernizing new technologies and devices that allow the production of modern and technologically reliable and high-quality products. Particular attention is paid to the improvement of high-performance cotton cleaning machines and the creation of resource-saving technologies in the field of world cotton cleaning. One of the main tasks of the industry is to improve the technical and economic indicators of cotton ginning enterprises, increase production efficiency and prevent losses of the resulting textile raw materials to produce high-quality cotton fiber, lint and seeds.